How do you express (11x-2) /( x^2 + x-6)11x2x2+x6 in partial fractions?

1 Answer
Feb 7, 2016

7/(x+ 3 ) + 4/(x - 2 )7x+3+4x2

Explanation:

First step is to factorise the denominator

x^2 + x - 6 = (x+3)(x - 2 ) x2+x6=(x+3)(x2)

since these factors are linear then the numerators will be constants.

(11x - 2 )/((x + 3 )(x - 2 )) = A/(x + 3 ) + B/(x - 2 ) 11x2(x+3)(x2)=Ax+3+Bx2

multiply both sides by (x + 3 )(x - 2 )

hence : 11x - 2 = A(x - 2 ) + B(x + 3 )..............(1)

Task now is to find A and B .Note that if x = 2 , the term with A will be zero and if x = - 3 the term with B will be zero.

let x = 2 in (1) : 20 = 5B rArr B = 4B=4

let x = -3 in (1): - 35 = - 5A rArr A = 7A=7

rArr (11x - 2)/(x^2 + x - 6 ) = 7/(x + 3 ) + 4/(x - 2 ) 11x2x2+x6=7x+3+4x2